KAJIAN PENANGANAN KERUSAKAN JALAN NASIONAL DI PULAU TIMOR DENGAN TEKNIK "MOISTURE BARRIER" - G.J. Winston Fernandez (Jurnal Jalan-Jembatan, 2007)
The damage of asphalt pavement occurs in national road between Kupang adn Atambua in Timor Island is East Nusa Tenggara usually identified by longitudinal cracks on side of road pavement. The cracks were caused by shrinkage and swelling of subgrade of "Bobonaro Clay" which has expansive characteristic. One methods from several possibilities to overcome the swell and shrinkage from happening, is to maintain the m.c. as constant as possible. The technology applied here is by the used of moisture barrier namely geomembran. This method was chosen to overcome the crack problem in Sta.214-217 between Maubesi - Nesam considering that the function for public service of the road should be kept functioning etc. After two years monotoring, no cracks detected. Keywords : expansive soils, moisture barrier, geomembrane.